Measuring the impacts of local land-use policies on vehicle miles of travel: The case of the first big-box store in Davis, California - Kristin Lovejoy; Gian-Claudia Sciara; Deborah Salon; Susan L Handy; Patricia Mokhtarian (Journal of Transport and Land Use)
Concerns over climate change have brought new impetus to the goal of reducing vehicle travel through land-use policy. To determine the degree to which land-use policies are effective in reducing vehicle travel, studies are needed that measure and compare vehicle travel both before and after a land-use policy change. The opening of the first big-box retail store in Davis, California, represented a major change in the retail landscape and an unusual opportunity to study its effect on shopping travel. Surveys of residents' shopping behavior conducted before and after the opening of the store revealed a significant shift in where people shopped and a measurable reduction in overall vehicle miles traveled (VMT) for shopping. Although the observed change in VMT is specific to the Davis context, the findings support the general proposition that bringing retail destinations closer to residences could help reduce vehicle travel, particularly where the comparable alternatives for the newly introduced store are far away. The study also offers important insights into the challenges of conducting before-and-after studies of the impact of local land-use changes.